Spectroscopic analysis of heavy metal in frozen shrimp from different seafood processing plants of Chittagong, Bangladesh - Ali, Mohammad Shaokat; Saha, Suvanker; Ahmed, Shamima; Uddin, Md Forhad; Yeasmin, Nilufa (Asian Journal of Medical and Biological Research, 2017)
This study is carried out to determine the level of three common heavy metals i.e. mercury (Hg), lead (Pb) and cadmium (Cd) from different branded frozen shrimp samples from different processing plants in Chittagong Metropolitan Area, Bangladesh. The level of heavy metals is investigated by using Atomic Absorption Spectrophotometer (AAS) in twenty different frozen shrimp samples from four different processing plants. The range of mean level of concentration (mg/kg) of mercury (Hg), lead (Pb) and cadmium (Cd) are 0.011-0.042 mg/kg, 0.065-0.087 mg/kg and 0.024-0.081 mg/kg respectively. Lead (Pb) has the highest mean concentration of 0.087 mg/kg while mercury has the lowest mean of 0.011 mg/kg. The mean concentration of mercury (Hg), lead (Pb) and cadmium (Cd) in shrimps was observed within the range of BSTI (Bangladesh Standards and Testing Institution) standards for aquatic foods. Asian J. Med. Biol. Res. December 2016, 2(4): 513-517